Risk of Arrhythmias in Endurance vs Strength Sports: A Comparative Review - Nawrat, Natalia Agata; Karbowiak, Krzysztof; Makselan, Natalia; Wijas, Daniel; Anczyk, Antoni; Handzel, Karolina; Kozdra, Bartłomiej; Kluś, Michał; Olszok, Mikołaj (Quality in Sport, 2026)
Background. While physical activity is vital for cardiovascular health, high-intensity competitive training follows a "J-shaped" dose-response curve for arrhythmic risk, driven by complex structural and electrical adaptations. Aim. To contrast the incidence, mechanistic pathways, and diagnostic patterns of arrhythmias in endurance versus strength-trained athletes. Materials and Methods. Data were synthesized from master endurance athletes, "power" phenotypes, and reference cohorts. The review evaluated diagnostic efficacy across athlete-specific ECG criteria, Holter monitoring, exercise stress testing, and advanced imaging, specifically echocardiography and Cardiac Magnetic Resonance (CMR) with late gadolinium enhancement. Results. Endurance athletes show a 2.5-fold higher risk of Atrial Fibrillation (AF) compared to controls, attributed to bi-atrial enlargement, fibrosis, and vagal dominance. Conversely, strength athletes exhibit a more benign supraventricular profile, with high muscle strength potentially buffering against bradyarrhythmias. While ventricular ectopy is common in both groups, endurance training is more closely linked to chronic right-ventricular (RV) remodeling and non-ischemic myocardial fibrosis. Modern ECG criteria provide high screening specificity, but CMR is the gold standard for identifying the "concealed scars" that provide a substrate for malignant events. Conclusion. The "Athlete’s Heart" is not a singular entity. Endurance training imposes an "atrial tax" of increased AF risk via volume-load adaptations, whereas strength-focused pressure-load training leads to concentric hypertrophy with fewer arrhythmic consequences. Regardless of modality, non-ischemic myocardial fibrosis remains the most potent predictor of life-threatening ventricular events.